PERAN GURU BIMBINGAN KONSELING DALAM MENANGGULANGI SISWA KORBAN RISAK DI SMA NEGERI 4 PALU - Febrianti, Febrianti; Handayani, Andi Muthia Sari (Program Studi Bimbingan dan Konseling Islam IAIN Palu, 2020)
The Objective of this research is to determine the role of teachers in counseling guidance dealing with students who are victims by risak at SMA Negeri 4 Palu. This research is classified as qualitative research, and the data were described both in written and spoken. This research was conducted in order to see the role of counseling guidance teacher in overcoming the risak victims at SMA Negeri 4 Palu. Furthermore, the data collection methods used in this reasearch are observation, interviews, and documentation. Then the data processing and analysis techniques were carried out through three stages, namely: data reduction, data presentation and conclusion drawing. This study was conducted to check the validity of the data using trigulation techniques.